2017
DOI: 10.1111/bjd.15702
|View full text |Cite
|
Sign up to set email alerts
|

Underreported use of palliative care and patient-reported outcome measures to address reduced quality of life in patients with calciphylaxis: a systematic review

Abstract: Calciphylaxis is associated with significant morbidity and mortality. Palliative care (PC) is a subspecialty that treats the pain and stress of serious illness. To assess whether the role of quality of life (QoL) indices, patient-reported outcome measures and PC have been studied in patients with calciphylaxis, we performed a systematic literature review. Several databases were searched from inception to October 2016 according to modified Preferred Reporting Items for Systematic Reviews and Meta-Analyses crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…These findings are similar to observations in the literature. A systematic review of 12 calciphylaxis studies concluded that there was no formal study of palliative care in patients with calciphylaxis, illustrating the need for the development of a calciphylaxis specific patient-reported outcome measure which would help to prompt earlier and more frequent palliative care consultations [ 9 ]. The utility of palliative care consultations in the end of life care of 24 ESRD patients with calciphylaxis was reported by Olarinan et al This study showed palliative care physicians were consulted in only 50% of the patients, with 54% receiving intensive care admission during the terminal phase of their illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are similar to observations in the literature. A systematic review of 12 calciphylaxis studies concluded that there was no formal study of palliative care in patients with calciphylaxis, illustrating the need for the development of a calciphylaxis specific patient-reported outcome measure which would help to prompt earlier and more frequent palliative care consultations [ 9 ]. The utility of palliative care consultations in the end of life care of 24 ESRD patients with calciphylaxis was reported by Olarinan et al This study showed palliative care physicians were consulted in only 50% of the patients, with 54% receiving intensive care admission during the terminal phase of their illness.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence suggests that pain management in calciphylaxis is unsatisfactory with differing practice across the United Kingdom (UK) and internationally [ 9 ]. A knowledge and practice survey was conducted to obtain information on physicians current practice of the management of pain in patients with calciphylaxis in the UK and the Republic of Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…These ndings are similar to observations in the literature. A systematic review of 12 calciphylaxis studies concluded that there was no formal study of palliative care in patients with calciphylaxis, illustrating the need for the development of a calciphylaxis speci c patient-reported outcome measure which would help to prompt earlier and more frequent palliative care consultations (9). The utility of palliative care consultations in the end of life care of 24 ESRD patients with calciphylaxis was reported by Olarinan et al This study showed palliative care physicians were consulted in only 50% of the patients, with 54% receiving intensive care admission during the terminal phase of their illness.…”
Section: Discussionmentioning
confidence: 99%
“…sodium thiosulphate, cinacalcet, and antibiotics), surgical (e.g. parathyroidectomy, wound debridement, and amputation) and modi cation of dialysis regimens such as varying dialysate calcium concentrations and increasing dialysis frequency (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…CUA, also referred to as calciphylaxis, is a thrombotic disorder of the skin and subcutaneous tissue [7,8]. Reported patient symptoms included pain, skin lesions, and pruritus [9]. STS is one of the cornerstones of calciphylaxis therapy and has been used for over 10 years for this indication, although this use remains off-label [9].…”
Section: Introductionmentioning
confidence: 99%